Analisis Laba Kotor Sebagai Alat Untuk Menentukan Naik Turunnya Harga Jual Pada Qmart Superstore Kota Gorontalo - Muhammad Ardi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
The problem happen in many companies is companies which often underestimate gross profit they obtain, so the company only focuses in net profit. But if it sees deeper, gross profit is able to describe the management itself, especially to determine the rise and fall of the sale price. The aim of this research is to investigating the gross profit in determine the rise and fall of the sale price in Qmart Superstore Gorontalo. The research method is taking 10 indofood products as sample of whole products. The price sale and main price Sun BC Beras Merah 8x20 Gr, Indomilk Full Cream 800 Gr, La Fonte Sphagetti 500 Gr, Chitato Beef Barbeque 68 Gr, Promina Biscuit Susu 130 Gr, Qtela Original 185 Gr, Happy Salad Pure Soya Oil 5 Ltr, Bu Krim Oxy Clean Higienis 750 Gr and Indomilk Instant 400 Gr is increase from 2014 to 2017. Wherease products Bimoli classic 5 Ltr is decrease in 2016 and increase in 2014, 2015, and 2017. The quantity of sale and main price of Sun BC Beras Merah 8x20 Gr, Indomilk Full Cream 800 Gr, La Fonte Sphagetti 500 Gr, Chitato Beef Barbeque 68 Gr, Promina Biscuit Susu 130 Gr, Qtela Original 185 Gr, Happy Salad Pure Soya Oil 5 Ltr, Bu Krim Oxy Clean Higienis 750 Gr and Indomilk Instant 400 Gr is changing in flexibility from 2014-2017. The change of sale quantity is cause by the consumer and the price sale itself.